The Influence of Teacher Self-Efficacy on Teacher Performance Through Organizational Learning - Elfira, Elfira; Maisyaroh, Maisyaroh; Sumarsono, Raden Bambang (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2024)
Abstract: This study aims to investigate the influence of teacher self-efficacy on teacher performance through organizational learning. The research employs a quantitative analysis approach using multiple linear regression analysis with SPSS 25 and SMART PLS 3. The population consists of 111 teachers from five schools in Sinjai Regency, from which a sample of 111 respondents was obtained through proportional sampling techniques. The findings indicate that teacher self-efficacy affects teacher performance, supporting the first hypothesis. However, the second hypothesis is rejected as organizational learning does not influence teacher performance. Lastly, the third hypothesis is rejected, indicating that teacher self-efficacy on teacher performance through organizational learning does not have an effect; teacher self-efficacy will not enhance teacher performance after reducing organizational learning.Keywords: teacher self-efficacy, teacher performance, merdeka belajar curriculum, organizational learning